The Georgia Memory Net: Implementation of a statewide program to diagnose and treat Alzheimer's disease and related dementias. Issue 4 (8th February 2022) - Bender, Alexis A.; McIntosh, Rebecca L.; Sudduth, Sean; Harris, Michaela; Tuckey, Kathy; Morgan, John C.; Jungerman, Joanna M.; Cox, Abby; Moore, Miranda A.; Ingram, Bryshia; Pier, Ellyn; Johnson, Theodore M.; et al.
Abstract: Objectives: The number of people living with dementia is growing and most patients go years without receiving a specific diagnosis or support services, leading to suboptimal care, negative impacts on the quality of life, and increased costs of care. To address these gaps, the State of Georgia Department of Human Services collaborated with academic and community partners to create the Georgia Memory Net (GMN). Design: GMN is a hub and spoke model partnered with Emory University's Cognitive Neurology Clinic and Emory Goizueta Alzheimer's Disease Research Center to provide training and support for best practices in diagnosis and management to Memory Assessment Clinics (MACs) throughout the state. Setting: Communities across the State of Georgia. Participants: GMN is a mix of academic and community providers, hospital systems, state and community agencies. Patients and families are evaluated at the MACs and connected to community services. Intervention: A dedicated clinic workflow: primary care providers (PCPs) identify a memory problem and refer to the MACs for diagnostic evaluation; meeting with a community services educator, and development of a care plan. The patient is reconnected with the PCP for continuity of care. Measurements: Initial metrics include numbers of unique patients, total patient visits, and referrals to state agency partners for community services. Results: GMN established five MACs across Georgia with annual state funding. Partners at Emory University provided initial training; refined patient workflows for best practices; and provide ongoing support, guidance, and continuing education for MAC teams. Local PCPs and community services partners demonstrated strong engagement with the new model. Conclusions: GMN is an innovative care model to improve access to accurate and timely diagnosis in patients with memory loss. GMN may help improve the quality of life for patients and families through preventive and early care.